Guttiferones: An insight into occurrence, biosynthesis, and their broad spectrum of pharmacological activities - Conceição, Mariana [UNESP]; Beserra, Fernando Pereira [UNESP]; Aldana Mejia, Jennyfer Andrea; Caldas, Gabriel Rocha; Tanimoto, Matheus Hikaru; Luzenti, Andréia Marincek; Gaspari, Priscyla Daniely Marcato; Evans, Nicholas David; Bastos, Jairo Kenupp; Pellizzon, Cláudia Helena [UNESP] (Elsevier, 2023)
Guttiferones belong to the polyisoprenylated benzophenone, a class of compounds, a very restricted group of natural plant products, especially in the Clusiaceae family. They are commonly found in bark, stem, leaves, and fruits of plants of the genus Garcinia and Symphonia. Guttiferones have the following classifications according to their chemical structure: A, B, C, D, E, F, G, H, I, J, K, L, M, N, O, P, Q, R, S, and T. All of them have received growing attention due to its multiple biological activities. This review provides a first comprehensive approach to plant sources, phytochemical profile, specific pharmacological effects, and mechanisms of guttiferones already described. Studies indicate a broad spectrum of pharmacological activities, such as: anti-inflammatory, immunomodulatory, antioxidant, antitumor, antiparasitic, antiviral, and antimicrobial. Despite the low toxicity of these compounds in healthy cells, there is a lack of studies in the literature related to toxicity in general. Given their beneficial effects, guttiferones are expected to be great potential drug candidates for treating cancer and infectious and transmissible diseases. However, further studies are needed to elucidate their toxicity, specific molecular mechanisms and targets, and to perform more in-depth pharmacokinetic studies. This review highlights chemical properties, biological characteristics, and mechanisms of action so far, offering a broad view of the subject and perspectives for the future of guttiferones in therapeutics.
Keywords: Benzophenone; Effects; Guttiferones; Mechanisms; Synthesis